Civility and Trust in Social Media - Angelo Antoci; Laura Bonelli; Fabio Paglieri; Tommaso G. Reggiani; Fabio Sabatini (Institute of Labor Economics (IZA), 2018)
Social media have been credited with the potential of reinvigorating trust by offering new opportunities for social and political participation. This view has been recently challenged by the rising phenomenon of online incivility, which has made the environment of social networking sites hostile to many users. We conduct a novel experiment in a Facebook setting to study how the effect of social media on trust varies depending on the civility or incivility of online interaction. We find that participants exposed to civil Facebook interaction are significantly more trusting. In contrast, when the use of Facebook is accompanied by the experience of online incivility, no significant changes occur in users' behavior. These results are robust to alternative configurations of the treatments.
Keywords: C91; D9; D91; Z1; 330; social media; Facebook; online incivility; trust; social networks; cooperation; trust game